The effect of melatonin on adrenal gland and pancreas function in alloxan – induced diabetes in adult female rabbits: Intisar Arar Taher 1 and Jawad Kadhim Arrak2 - Taher, Intisar Arar (The Iraqi Journal of Veterinary Medicine, 2016)
The present study was carried out to investigate the ameliorative effect of melatonin on pancreatic and adrenal dysfunction induced by alloxan in adult female rabbits. Twenty four adult female rabbits were randomly divided into four equal groups treated for 42 days as follows: control group received 2 ml of distal water intraperitoneally, animals of the second group received single dose of 150 mg /kg of alloxan (group T1), while the third group received single dose of 150 mg/kg of alloxan and after 7 days received 10mg/kg I/P of melatonin for 42 days of experiment (T2 group). The fourth group received 10 mg/kg I/P of melatonin for 42 days .After the 7 days of alloxan injection the blood is collected from (T1) and (T2) animals, to investigate of diabetes induction in these groups. Also blood samples were collected at zero time, 14, 28 and 42 days of the experiment for measuring the serum concentration of glucose, total protein, total cholesterol, reduce glutathione and hormones concentration (insulin and cortisol). The result of present study indicated that melatonin administration is not affected in body weight in rabbits to T2 and T3 as compared with control group, while (T1) group showed significant decrease in these parameters as compared with other groups. The adrenal gland weight to body weight ratio showed significant increase in adrenal weight in (T1) as compared with all other group while T2 and T3 groups showed significant decrease as compared with T1 groups. While the pancreas gland weight to body weight ratio showed significant increase in pancreas weight in (T3) group as compared with other groups. Animals T1 and T2 groups showed significant decrease as compared with T3 and control groups. Animals T1 group showed significant elevation in serum glucose, total cholesterol and serum cortisol concentration as compared with control, T2 and T3 groups. The results also showed a significant decrease in total serum protein, serum insulin and reduce glutathione concentrations in alloxan treated group (T1) as compared with control, T2 and T3 animals. Inferred from the result of this experiment is treatment of diabetic female rabbits with melatonin (10 mg /kg .B.W) for 42 days lead to improve the function of adrenal gland and pancreas gland. Also it showed the possibility of reducing oxidative stress triggered by alloxan through the use of melatonin.